Effectiveness of Wordwall Learning Media in Enhancing Students’ Ability to Write Formal Letters in Indonesian Language Learning - Sely Ariska; Auwliya Khairun Nisa (JPI: Jurnal Pustaka Indonesia, 2024)
Writing official letters is one of the essential competencies in Indonesian language education, yet many students struggle to master its structural and linguistic conventions when taught through traditional methods. This study aimed to examine the effectiveness of Wordwall as a digital gamified learning medium in improving seventh-grade students’ ability to write official letters at SMP Negeri 13 Bengkulu City. Using a quasi-experimental design with a control and experimental group, data were collected through pretests, posttests, and classroom observations, with the experimental group receiving Wordwall-based instruction and the control group taught using conventional approaches. The results showed that students in the experimental class achieved significantly higher posttest scores than those in the control class, with N-Gain values ranging from medium to high, demonstrating measurable improvement in their writing performance. The findings confirm that Wordwall not only increases student engagement and motivation but also facilitates mastery of formal writing skills through interactive and enjoyable learning experiences. The implication of this research is that integrating gamified digital tools such as Wordwall into language instruction can serve as an effective strategy for enhancing students’ academic literacy, supporting curriculum innovation, and informing future policy on digital learning integration in schools.